Suffering in Life Causing Loss of Faith in Tortuga by Rudolfo Anaya - Juliansyah, Juliansyah; Minderop, Albertine; Beresaby, Rheinatus Alfonsus (Universitas Muhammadiyah Gorontalo, 2025)
The purpose of this study is to demonstrate that the novel “Tortuga” expresses the idea that poverty and suffering experienced by Tortuga and his friends make them loss faith to God. Hermeneutics and content analysis are the research methods employed in this study. The process of examining the author's ideas through the remarks, queries, and exchanges between characters is known as content analysis. This approach aims to reveal, comprehend, and assimilate the meaning contained in literary works. The techniques of Hermeneutics, a philosophy of interpretation, are the method of interpretation employed in this study. The most effective method for interpreting literary and philosophical materials is hermeneutics. The study design entails the interpretation of deeply understood figurative language, or imagery. This allows the researcher to fully grasp the meaning found in literature since they possess comprehensive knowledge of the culture, religion, and history in addition to language and literature. The outcome of the study is the collection of phrases and sentences that contain the characters’ experience relating to sufferings and their viewpoint of God. The discussion of the research is the study of characters’ reasoning and questions of God’s existence. The novelty of this research is that the usage of both content analysis and hermeneutics. For hermeneutics itself, the research covers several points including history.